Building Biomedical Materials using Photochemical Bond Cleavage. (5th February 2015) - Bao, Chunyan; Zhu, Linyong; Lin, Qiuning; Tian, He
<x xml:space="preserve">Abstract</x> Light can be used as an external trigger to precisely determine where and when a process is initiated as well as how much of the process is being consumed. Phototriggers are a type of photoresponsive functional group that undergo an irreversible photolysis reaction by selectively breaking a chemical bond, enabling three fundamental functions: the photoactivation of fluorescent and bioactive molecules; the photocleavable degradation of macromolecular materials; and the photorelease of drugs, active groups, or surface charges from carriers and interfaces. With the expanded applications of light‐controlled technology, particularly in living systems, new challenges and improvements of phototriggers are required to fulfill the demands for better sensitivity, faster kinetics, and more‐demanding biomedical applications. Here, improvements to several conventional phototriggers are highlighted, and their notable, representative biomedical applications and their challenges are discussed.